Somaticismo y socio-psicologismo en el desarrollo histórico de la psiquiatría desde el siglo XVII (2001)
ABSTRACT: In this work different conceptions of mental illness as well as its influences on institutions devoted to the care of those patients between century XVII and nowadays are reviewed. The emphasis was put on public health and administrative aspects and not on specialized psychiatric items. There were used secondary bibliography. It is shown that somatic and psycho-social explanations of mental illness has been assumed alternatively throughout the period by alienists and psychiatrists, determining different types of facing the treatment of madness, without getting a definite agreement.